Single-Inhaler Triple Therapy in Primary Care Across Europe: Expert Panel Consensus on the Consequences of Payer-Driven Access Rules and Call to Action - Di Marco F; Shahaj O; Valipour A; Legrand B; Jommi C; Micheletto C; Vogelmeier CF; Freeman D; Kocks JWH; Alves L; Rubio MC; Peché R; et al. (International Journal of COPD)
Fabiano Di Marco,1 Orjola Shahaj,2 Arschang Valipour,3 Bertrand Legrand,4 Claudio Jommi,5 Claudio Micheletto,6 Claus Franz Vogelmeier,7 Daryl Freeman,8 Janwillem WH Kocks,9 Luis Alves,10 Myriam Calle Rubio,11 Rudi Peché,12 Susanna Palkonen Snr,13 Tonya Winders,14 Nicolas Roche15 1Department of Health Sciences, Università Degli Studi Di Milano, Milan, Italy; 2Aquarius Population Health, London, UK; 3Department of Respiratory and Critical Care Medicine, the Karl-Landsteiner-Institute for Lung Research and Pulmonary Oncology, Vienna, Austria; 4Lille University Hospital Centre, Lille University, Lille, France; 5Department of Pharmaceutical Sciences, Università degli Studi Del Piemonte Orientale, Novara, Italy; 6Respiratory Division, Università Di Verona, Verona, Italy; 7Department of Pulmonology, University Hospital Marburg, Marburg, Germany; 8Norfolk Community Health and Care, Norwich, UK; 9Department of Pulmonology, University of Groningen, Groningen, the Netherlands; 10EPIUnit Instituto de Saúde Pública, Universidade Do Porto, Porto, Portugal; 11Pulmonology Department, Instituto de Investigación Sanitaria Del Hospital Clínico San Carlos (Idissc), Madrid, Spain; 12Pulmonology Department, Charleroi, Belgium; 13European Federation of Allergy and Airways Diseases Patients Associations (EFA), Brussels, Belgium; 14Global Allergy & Airways Patient Platform, Vienna, Austria; 15Respiratory Medicine, Paris Cité University, Paris, FranceCorrespondence: Orjola Shahaj, Aquarius Population Health, Unit 16 Tileyard Studios, London, N7 9AH, UK, Tel +44 207 993 2930, Email orjola.shahaj@aquariusph.comBackground: Chronic obstructive pulmonary disease (COPD) is a prevalent condition characterized by persistent airflow obstruction and respiratory symptoms. Single-Inhaler Triple Therapy (SITT) has been shown to improve patient adherence, reduce exacerbations, and lower healthcare resource utilization in patients who are not controlled despite being on dual therapy or Multiple-Inhaler Triple Therapy (MITT). Despite evidence supporting SITT, payer-driven access rules across Europe sometimes limit its use in primary care, creating barriers to optimal COPD management.Purpose: Through expert consensus, the study seeks to generate a shared understanding of the unintended consequences of payer-driven access criteria for SITT in managing moderate-to-severe COPD in primary care.Methods: A targeted literature review (TLR) was conducted to assess SITT initiation in primary care across Europe and examine the impact of access criteria. Semi-structured interviews were held with 14 experts from nine European countries, including clinicians, health economists, and patient advocacy representatives. A consensus generation workshop was conducted, where experts evaluated the findings and developed position statements to highlight the challenges posed by payer-driven access criteria.Results: The TLR identified variability in access to SITT in Europe, with several countries restricting its initiation to specialists, thus limiting primary care physicians’ (PCPs) ability to prescribe SITT. The expert panel generated seven consensus points stating that enabling PCPs to step up or switch eligible patients to SITT has the potential to support care continuity, enhance clinical autonomy for PCPs, reduce reliance on potentially less effective treatment options, improve patient and healthcare system outcomes, avoid unnecessary referrals to specialists, enable prompt initiation of guideline-directed medical therapy for COPD in primary care and reduce access inequalities.Conclusion: Restrictions for SITT initiation in primary care may need to be revisited to mitigate their unintended health and cost consequences and improve equitable access to treatment. This should take into consideration each country’s unique healthcare system.Keywords: COPD, single-inhaler triple therapy, payer, access, reimbursement, primary care, expert consensus